Consumption Ideology - Schmitt, Bernd; Brakus, J Joško; Biraglia, Alessandro (Journal of Consumer Research, 2022)
AbstractIdeology plays a central role in consumer decisions, actions, and practices. While there have been numerous studies of ideological formations in specific consumption contexts, an integrative theoretical framework on consumption ideology has been missing. The theoretical framework presented in this article integrates systemic, social group, and social reality perspectives from social theory with prior consumer research to conceptualize consumption ideology as ideas and ideals that are related to consumerism and manifested in consumer behavior. Consumption ideology originates from conflicts between consumer desires and the system of consumerism. It is reflected in consumers’ lived experiences and expressed in social representations and communicative actions related to status-based consumption, brand affinity and antipathy, performed practices, and political consumption. By adapting to the market, consumers confirm the system, but when they resist, they accelerate conflicts in consumer experiences unless resistance is ideologically co-opted by the market. Three illustrative cases—upcycling, Zoom backgrounds, and the commercialization of TikTok—exemplify how the framework may be used to analyze consumption ideology and generate new research questions. The article concludes with future research programs that move beyond micro-theorizations to illuminate the broader role of ideology in contemporary consumerist society.